MEASURING THE OUTCOMES OF HISTORY TEACHING: AN EMPIRICAL STUDY OF HISTORICAL CONSCIOUSNESS (Historia, 2021)
The first comprehensive attempt to measure the outcomes of history teaching for adolescents was published in Hamburg in 1997. The research is based on the assumption that the development of an historical consciousness is the most important long-term life skill that history teaching imparts to students.
Keywords: historical consciousness; Europe; Netherlands; society; education; Department of History; University of Stellenbosch; Germany; Bergen College of Higher Education; University of Hamburg